Psychological Factors that Influence the Health of People with Hemophilia - Luis Horacio Aguiar Palacios; Ana Gabriela Magallanes Rodríguez; Julio Román Martínez Alvarado; Denisse Ariana Osuna Encinas (Revista Finlay, 2025)
Chronic diseases are the predominant cause of death worldwide. They affect people of all ages, genders, and ethnicities. They are non-contagious, progress slowly, and develop due to hereditary factors, environmental influences, or unhealthy lifestyle habits. They adversely affect the quality of life of those who suffer from them, limiting their daily functioning and emotional well-being. Hemophilia is a chronic disease that significantly impacts the quality of life of the patient and their family. Suffering from hemophilia involves continuous adjustments and modifications in lifestyle habits, which can negatively affect psychological well-being, generating stress, low self-esteem, and depression. This study analyzes the psychological factors that influence the perception of quality of life of people with hemophilia, with the purpose of identifying alternatives for their overall well-being and improving their quality of life.